Perovskite–Quantum Dot Structures in Solar Cells: Materials, Properties and Emerging Trends (Comprehensive Journal of Science, 2026)
The rapid development of perovskite–quantum dot (PQD) structures has opened new avenues for high-efficiency, low-cost solar cells. This descriptive study systematically synthesizes existing literature on PQDs, focusing on material composition, synthesis strategies, optical and electrical properties and device integration approaches. The study identifies key trends, including the tunability of bandgaps through halide composition, the critical role of surface ligands in charge transport and stability and the emerging preference for hybrid device architectures. Challenges related to environmental stability, reproducibility and scalability are also discussed. The findings highlight the potential of PQDs for next-generation photovoltaics and provide recommendations for future research aimed at improving performance, sustainability and practical applicability.